GEOGRAFIS KAWASAN EKOWISATA PRPM “TRACKING MANGROVE IN LOVE” - Koto, Arthur Gani; Taslim, Ivan; Indrianti, Merita Ayu (Program Studi Pendidikan Geografi STKIP PGRI Sumatera Barat, 2020)
One of the coastal areas including the mangrove forest, storing great potential to be used sustainably in addition to its function also as a carbon stock storage. Mangrove forests become one of the attractions to be used as an ecotourism area accompanied by local cultural concepts. This study aims to geographically analyze the